Editorial - Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2019)
Indian education system is the oldest. With changing times the system has also changed. The moot question is "In this education system what and where is the role of faculty?" Faculty is a vital component of Education System because the Input, Process, and Output everything is dependent on the performance of the faculty. If we want our Institute to be NBA, NAAC accredited or we wish to benchmark ourselves in NIRF ranking survey the important element is Faculty performance and involvement that is derived from Academic Leadership.